The Efficacy of Integrated Diabetic Program on Glycemic Control in Type 2 Diabetic Patients - Sathukhun, Vanida (Journal of Health Science of Thailand, 2018)
This study was carried out as quasi-experiment with the objective of evaluating the efficacy of an integrated diabetic program (IDP) on glycemic control in type 2 diabetic patients receiving only oral hypoglycemic drug treatment at the out patient diabetic clinic of the 17th Somdej Prasungkaraj hospital, Suphan Buri. Eighty patients, aged 35-50 years, were enrolled. Subjects were divided into 2 groups; group I underwent IDP. The program consisted of health and nutrition education provided by staff nurses for 10 days with additional focus group discussion. Subjects were also encouraged to increase their physical activities through brisk walking for 30 minutes every day. For 2 weeks, IDP was provided to subjects who continued to practice the brisk walking even 4 weeks afterward. Group II was a control group undergoing normal treatment at OPD. Other inclusion criteria were; all enrolled subjects having FBS 130-200 mg/dl, their duration of diabetes were less than 10 years without any complications related to the disease as shown by normal results of their physical examination, blood pressure measurement, chest x-ray, EKG, electrolyte, BUN/Cr and UA in all subjects. Fasting blood sugar (FBS), HbA1c and lipid profile were also determined at baseline and at the 6th week. Results showed that mean difference of pre-post FBS of the group I at 6th week, 37.0, SD 14.9 mg/dl, was significantly lower; and was significantly lower than that of group II by 24.6, SD 11.7 mg/dl. Mean serum HbA1c, total cholesterol, triglycerides, LDL-C-cholesterol and HDL-Ccholesterol were not significantly reduced compared to those of baseline and group II. Improved diabetes knowledge scores were noted in both groups but mean knowledge scores were not significantly different between the 2 groups. It was suggested that IDP could be applied for patients with type 2 DM who were poorly controlled by medicine alone. IDP program provided more practical knowledge and learning experience with emphasis on continuing in increaseing physical activity for 6 weeks. The program provided the improved fasting FBS profile that reflected good prognosis of the disease, if prolonged further, also might contribute to further improv lipid profile.